2018
DOI: 10.13033/isahp.y2018.027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health-Care Waste Treatment Technologies Based on Analytic Network Process

Abstract: The safety of health-care waste(HCW) treatment is an important part of maintaining the health of the group, and it is very crucial to choose an appropriate method of HCW management. Based on the understanding of the HCW disposal methods and the consideration of the interdependence of indicators, the objective of this paper is to give a reasonable evaluation of the HCW treatment alternatives by using Analytic Network Process (ANP). Finally, steam sterilization is the best method of HCW management at this stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Aunkrisa Sangchumnong surveyed the Klang mangrove tourist attractions in Central Thailand through participatory action research, summarized four important characteristics of the tourism resources in the area, and proposed four key points for the development of the area, one of which is to adhere to sustainable tourism [4]. Chen Jianbo selected 23 indicators from four aspects of landscape value, health value, environmental conditions, and development conditions to construct an evaluation index system for health tourism resources [5]. Through a literature analysis, in-depth interviews, and field visits, Chen Zhiyong took the tourism resources of Tianlong Tunpu in Guizhou Province as an example for study and found that the composition characteristics of rural tourism resources and the particularity of human capital led to the difficult development of rural tourism property rights [6].…”
Section: Introductionmentioning
confidence: 99%
“…Aunkrisa Sangchumnong surveyed the Klang mangrove tourist attractions in Central Thailand through participatory action research, summarized four important characteristics of the tourism resources in the area, and proposed four key points for the development of the area, one of which is to adhere to sustainable tourism [4]. Chen Jianbo selected 23 indicators from four aspects of landscape value, health value, environmental conditions, and development conditions to construct an evaluation index system for health tourism resources [5]. Through a literature analysis, in-depth interviews, and field visits, Chen Zhiyong took the tourism resources of Tianlong Tunpu in Guizhou Province as an example for study and found that the composition characteristics of rural tourism resources and the particularity of human capital led to the difficult development of rural tourism property rights [6].…”
Section: Introductionmentioning
confidence: 99%